Increasing selection of and engagement in physical activity in children with autism spectrum disorder. Issue 4 (6th June 2022) - Goldman, Kissel J.; DeLeon, Iser G.
Abstract : Children with autism spectrum disorder (ASD) engage in reduced levels of physical activity relative to neurotypical children. Researchers conducted 2 studies to 1) evaluate the influence of the number of physical activity options and effort on choice and 2) develop a token‐based intervention to increase physical activity engagement and evaluate whether the opportunity to access the intervention supported responding similar to physical or sedentary activity alone. Four children with ASD participated. Additional physical activity options alone did not increase physical activity selection, but increased effort reduced selection of sedentary activity. Tokens increased physical activity for 2 participants. A combination of physical and sedentary activities maintained as much as or more responding than either activity in isolation for all participants. Limitations and potential areas of future research on choice and physical activity are discussed.